2013
DOI: 10.1016/j.jacc.2013.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Primary Results of the HABIT Trial (Heart Failure Assessment With BNP in the Home)

Abstract: This pilot study demonstrates that home BNP testing is feasible and that trials using home monitoring for guiding therapy are justifiable in high-risk patients. Daily weight monitoring is complementary to BNP, but BNP changes correspond to larger changes in risk, both upward and downward. (Heart Failure [HF] Assessment with B-type Natriuretic Peptide [BNP] In the Home [HABIT]; NCT00946231).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 23 publications
6
60
0
4
Order By: Relevance
“…A research project aimed to implement BNP monitoring in the home (the HABIT trial) showed that patients can be taught to take their own blood for testing [4]. The present finding of a stable relationship between relative changes in plasma and urinary concentrations of NT-proBNP over a period of HF treatment optimization opens the possibility of using urine analysis to monitor HF in the home care setting.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…A research project aimed to implement BNP monitoring in the home (the HABIT trial) showed that patients can be taught to take their own blood for testing [4]. The present finding of a stable relationship between relative changes in plasma and urinary concentrations of NT-proBNP over a period of HF treatment optimization opens the possibility of using urine analysis to monitor HF in the home care setting.…”
Section: Discussionmentioning
confidence: 63%
“…Changes in the amino-terminal pro-hormone brain natriuretic peptide (NTproBNP) level during in-hospital treatment are strong predictors of mortality and early readmission [2][3][4]; therefore, NT-proBNP levels might be successfully used to guide the treatment of HF patients. An increase in NT-proBNP concentration indicates a worsening of the condition and, together with worsening symptoms, may call for a period of hospitalization or intensified treatment in the patient's home [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BNP peptides are effective at diagnosing HF among patients with dyspnea [14], ruling out acute decompensated HF [15], and future adverse cardiovascular events and mortality among patients [36,37]. They are also used to guide HF therapy [8,38]. High sensitivity troponin release in the absence of coronary hypoperfusion is also a marker of ongoing myocyte injury and necrosis [39][40][41][42][43].…”
Section: Cs Distinguishes Failing Cardiac Muscle From Hf Comorbiditiesmentioning
confidence: 99%